Attacks on Vision or Communication? The Concepts of Enrique Pichon-Rivière and Hanna Segal - Ulrike Benal (EJP import test, 2024)
Summary The paper refers to the theoretical understanding of Enrique Pichon-Rivière and Hanna Segal by presenting a brief clinical sequence that focuses on the role of the eyes as a means of communication in the context of projective identification. Pichon-Rivière was one of the founding fathers of the Argentine Psychoanalytic Association and made a series of theoretical reflections that have been made accessible to a wider circle of psychoanalysts in recent years, as his work was only translated into English in 2017. Hanna Segal addressed the role of vision in one of her later papers, “Vision” (2007). In this paper, she also refers to a meeting with Pichon-Rivière in Buenos Aires in the 1950s. He drew her attention to the importance of the eyes for psychotic functioning, which seemed to leave a lasting impression on Segal and contributed to her further theoretical considerations. A patient's dream is used to show how the sense of sight is perverted and used in the service of defense. Projective identification via the eyes can be understood as an attempt to prevent communication, but at the same time this attack can also be understood as a form of communication. Pichon-Rivière's concepts of the 3 Ds and the role (2017a) are used to show how the clinical situation and, in particular, the role of the eyes could have been understood in this psychoanalytic situation. This paper examines how this understanding could have been further utilized via a greater inclusion of Pichon-Rivière’s work.
Keywords: 3 Ds; El Vínculo; Projective Identification; vision; Voyeurism